Numerical analysis to determine the technical water losses in a water supply system - Taseski, Goce; Nikola Krstovski (Gdańsk University of Technology Publishing House, Gdańsk 2022, 2022)
In N. Macedonia for many years, even decades, decreasing the capacities of water resources has been discussed, as well as increasing the specific water consumption per individual consumer. These circumstances of increased water consumption are directly related to, and caused by increased water losses in water supply system. The great losses in water supply systems, as well as ordered Non Revenue Water contribute to further restrict clean water supply. Namely, this contributes to increased amount of water entering the distribution system and additional unjustified investment in the capacities of supplied raw water, rather than investment into remodeling and subsequent management of the network. Recently, technological development facilitates a more active application of all available data; namely, the amount of information collected from water supply systems is increased, as well as the number of measurement points, the type of measurement data and the frequency of readings. As a result, control of water supply networks is improved, as well as knowledge for what in fact happens in the water supply systems. By using a measurement technique and by determining measurement points, we obtain data for the amount of water in water supply systems, which can be analyzed to determine the water losses in water supply systems. The measurements taken from the water supply system and the analysis of the experimental readings gave a full picture for the water loss state in the water supply system of Strumica. Leakages and pressure at specific measurement spots were also analyzed, and the total water loss and real losses on a daily and yearly basis were calculated, shown in percentage in relation to the water entering the distribution system in the water supply of Strumica.
Keywords: water supply systems; water losses; measurement points; analysis water losses